2023
DOI: 10.1007/s12583-021-1506-z
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Pseudokarstic Depressions on Mount Bocskor (Bakony Region, Hungary)

Abstract: Surface forms above the mine (Ármin mine) of Mount Bocskor (Southern Bakony, Hungary) were examined. We made contour maps, plan maps, morphological maps and atectonic grike (cave) maps of some of the forms and their surroundings. We examined the distribution of the depth, length, elongation ratio in case of some depressions, the relation between the depth and the diameter of some depressions, the relationship between depression group directions and mine cut directions, the standard deviation of the direction d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The material from the overlying beds is known to enter these fissures either by suffosion, leading to the formation of pseudokarstic suffosion dolines, or by collapse, resulting in pseudokarstic dropout dolines. Such mechanisms have been identified in the formation of subsidence dolines at Bocskor Hill in Hungary [27].…”
Section: Zone-specific Miningmentioning
confidence: 94%
See 2 more Smart Citations
“…The material from the overlying beds is known to enter these fissures either by suffosion, leading to the formation of pseudokarstic suffosion dolines, or by collapse, resulting in pseudokarstic dropout dolines. Such mechanisms have been identified in the formation of subsidence dolines at Bocskor Hill in Hungary [27].…”
Section: Zone-specific Miningmentioning
confidence: 94%
“…It is observed that mining operations in this region may target the extraction of karstic rock or minerals associated with karstic features. The diversity of infill within karst depressions is noted, ranging from bauxite [26] to iron ore [2], and including interbedded materials such as coal [27].…”
Section: Zone-specific Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…Mines may be excavated by underground mining or surface mining. Studies on the relationship between mining and karstic landscapes have become widespread [9][10][11][12][13]. In the Bakony Region, several studies have mentioned the relationship between mining and karst and paleokarst (for example) [14].…”
Section: Introductionmentioning
confidence: 99%
“…During karstification karst depressions (solution dolines), poljes and inselberg karst developed [5,8,9]. Its present surface karst is of an island-like pattern and covered karst that developed on blocks of medium elevation [10]. Features of its covered karst are suffosion dolines, but solution dolines also occur in small numbers at the margin of the mountains [10].…”
Section: Introductionmentioning
confidence: 99%